Analysis of Women's Multiple Roles and Domestic Violence Female Factory Workers in Sunggal District, Deli Serdang Regency - Melda Lubis (Talenta Publisher, 2022)
Multiple Roles is a work role that is accepted by one sex more than the other sex. The division of labor based on gender can be divided into 3 types, namely: Reproductive, Productive, and Social or also called 3 triple roles gender roles. The purpose of this study is to find out how multiple roles and domestic violence occur in Sunggal District, Deli Serdang Regency. This type of research is qualitative with descriptive methods. Data collection techniques in this study using primary data that is data obtained through observation and interviews and documentation. Primary data collection techniques using the method of observation, interviews, and documentation. The results showed that the Multiple Roles of women working as factory workers because of the insistence on the family's economic needs getting higher, meeting the needs of daily life, the husband does not work, Lack of husband's responsibility as the head of the household in meeting family needs, husband who do not have a permanent job but are unemployed who every day the husband of the wives of the factory workers spends his time from morning even to night only in the coffee shop / â€œtuakâ€.